Attenuation of pharmaceutically active compounds in aqueous solution by UV/CaO2 process: Influencing factors, degradation mechanism and pathways. (1st November 2019) - Zheng, Ming; Daniels, Kevin D.; Park, Minkyu; Nienhauser, Alec Brockway; Clevenger, Erica C.; Li, Yongmei; Snyder, Shane A.
Abstract: As freshwater sources continue to be influenced by wastewater effluents, there is a dire need to develop advanced water treatment processes capable of treating the wastewater-derived contaminants, especially for pharmaceutically active compounds (PhACs). Ultraviolet light (UV) combined with calcium peroxide (CaO2 ) as an advanced oxidation process (AOP) to attenuate five widespread PhACs (carbamazepine (CBZ), primidone (PMD), phenobarbital (PBB), thiamphenicol (TAP) and florfenicol (FF)) was investigated in this paper. The degradation of these compounds followed pseudo-first-order kinetics ( R 2  > 0.96). The optimum CaO2 dosage was 0.1 g L −1 and lower initial contaminants concentration was beneficial to their degradation. The UV/CaO2 treatment of test PhACs was attributed to the combination of UV/H2 O2 and UV-base-photolysis (UV/Ca(OH)2 ), and the degradation mechanism was recognized as both UV direct photolysis and indirect photolysis caused by reactive radicals (OH, triplet states of dissolved organic matter ( 3 DOM*), and 1 O2 ). Furthermore, the tentative transformation pathways of the five PhACs were proposed based on the detected intermediates and the degradation mechanisms. The final products of inorganic carbon and nitrogen indicate UV/CaO2 treatment can significantly mineralize test PhACs. Also, the CaO2 addition significantly reduced the energy consumption of UV irradiation according to electrical energy per order . The effective removal of CBZ and PMD in a secondary wastewater effluent by UV/CaO2 treatment demonstrates the potential use of this AOP technology in advanced treatment of wastewater-derived PhACs. Graphical abstract: Image 1 Highlights: UV/CaO2 can effectively remove PhACs in aqueous phase. .OH, 1 O2 and 3 DOM* were identified under UV/CaO2 treatment Ca(OH)2 played an important role in the removal of PBB, TAP and FF. The degradation pathways of test compounds were proposed. UV/CaO2 underwent a better removal of CBZ/PMD in WWE than UV/H2 O2 .